Facade, Videsh Dak Bhavan - Ghosh, Ayan (2023)
Videsh Dak Bhavan, also known as the Foreign Post Office (FPO), is in Irwin House, named after Lord Irwin, Viceroy of India (1926-31). The FPO facilitates the import and export of goods by Post Parcels. The Postal Department also provides access to Customs for examination, assessment, clearance, etc., of parcels that arrive via mail.